Simultaneous Aerosol and Ocean Properties From the PolCube CubeSat Polarimeter - Stamnes, Snorre; Baize, Rosemary; Bontempi, Paula; Cairns, Brian; Chemyakin, Eduard; Choi, Young-Jun; Chowdhary, Jacek; Hu, Yongxiang; Jeong, Minsup; Kang, Kyung-In; Kim, Sungsoo S.; Liu, Xu; et al. (Frontiers in Remote Sensing, 2021)
We quantify the performance of aerosol and ocean remote sensing products from the PolCube instrument using a previously-developed polarimeter retrieval algorithm based on optimal estimation. PolCube is a modified version of the PolCam lunar instrument on the Korea Pathfinder Lunar Orbiter (KPLO) that has been optimized for Earth-Science observations of aerosol, ocean, and thin cloud optical properties. The objective of the PolCube instrument is to retrieve detailed fine-mode (pollution and smoke) and coarse-mode (sea-salt and dust) aerosol properties over the ocean for a range of light to heavy aerosol loadings using its polarimetric-imaging capability at multiple angles and wavelengths from 410-865 nm. An additional objective is to discriminate aerosols from thin clouds. PolCube's retrieval performance of aerosol optical and microphysical properties and ocean products is quantitatively assessed. We estimate that PolCube can retrieve total aerosol optical depth (AOD) at 555 nm within +/- 0.068, fine-mode AOD within +/- 0.078, and fine-mode single-scattering albedo (SSA) within +/- 0.036, where all uncertainties are expressed as one standard deviation (1-sigma). PolCube's accurate and high-resolution aerosol-retrieval products will provide unique spatial and temporal coverage of the Earth that can be used synergistically with other instruments, such as the Geostationary Environmental Monitoring Spectrometer (GEMS) to improve air-quality forecasting.